Factors for the low publication of thesis in universities - Díaz-Lazo, Aníbal Valentín (2018)
The development of scientific publication, from the undergraduate level, is of vital importance to increase the scientific production of the Universities, especially in medical schools, and thus achieve greater visibility. The stimulus for the realization of research should be permanent, until it is published in an indexed scientific journal; since only in this way the process of scientific research is completed.